"We Are Not Fools": Online News Commentators' Perceptions of Real and Ideal Journalism. (January 2016) - Slavtcheva-Petkova, Vera
Twenty-five years after the fall of the Berlin Wall, Eastern European countries face an increasing threat to their media pluralism and democracies after a lot of media corporations fell in the hands of local owners. The region is plagued by "mini-Murdochs, " and Bulgaria is a case in point. This study investigates a subset of Bulgarian online newspaper readers' perceptions of the state of journalism. The article presents the results from a qualitative analysis of 1, 583 comments about the media war between the country's biggest press groups. It focuses on 178 comments that discuss the role of journalists. Readers differentiate between "ideal journalism" and "real journalism." The former is based on an idealized view of journalists as detached watchdogs, whereas the latter depicts a dire picture of journalists as manipulative servants of their owners. The virtual space is a vibrant arena for democratic discussions and can also potentially serve as an accountability tool for journalists. A reconceptualization of Habermas's public sphere is needed if we are to more clearly understand how vibrant online spaces contribute to democracy even if they fall short of his normative ideal.